Penerapan Pemberian Air Rebusan Daun Binahong terhadap Penyembuhan Luka Perineum Masa Nifas - Nabila Dewi Cahyani; Anjar Nurrohmah (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
Background : Childbirth is accompanied by perineal wounds in Indonesia as much as 75%. In 2022, there will be 12,145 cases of mothers experiencing perineal wounds in Central Java. In 2021, there were 255 cases of mothers experiencing perineal wounds in Boyolali (59.4%) from 429 deliveries. The process that occurs during normal delivery can cause perineal tears. Treatment of perineal wounds often uses binahong leaves to speed up healing of perineal wounds and prevent infection. Objective: To determine the effect of perineal wounds before and after being given boiled water from binahong leaves during the postpartum period. Method: Descriptive with application to 2 respondents. Respondents were given boiled water from binahong leaves from the first day to the eighth day post partum in a row. Results: After applying boiled water from binahong leaves for 8 consecutive days, the results showed a decrease in the rate of healing of perineal wounds in both respondents, there was a decrease in scores in Mrs. U and Mrs. A is 0 (good wound healing). Conclusion: There is an effect of giving boiled water from binahong leaves which can accelerate the healing of perineal wounds.